Salivary hormonal responses and performance changes during 15 weeks of mixed aerobic and weight training in elite junior wrestlers - Passelergue, P. A.; Lac, G. (The Journal of Strength and Conditioning Research, 2012)
To prepare efficiently for competition, wrestlers usually train physically for a period of approximately 12-20 weeks. Numerous physical qualities must be developed during this period of preparation: aerobic fitness, maximal strength, muscular endurance, power, and speed. However, numerous studies have concluded that it is difficult to concurrently develop strength and aerobic fitness for several reasons, in particular antagonistic endocrine variations. The study involved 15 elite junior wrestlers who trained at a sports training school for 15 weeks. To investigate the effects of long-term training and to assess the relationships between hormonal concentrations (salivary testosterone [T] and cortisol [C]) and performance changes during simultaneous strength and aerobic fitness training, 6 saliva samples and 3 physical tests and 2 measures of body composition were made during the training period. Wrestlers had a significant increase (+1.5 kg) in body weight without changes in percentage body fat. Apart from the 20-m maximal shuttle speed, all performances increased significantly during the 15 weeks of training: maximum mechanical power output (Pmax: +12.8%), mean power during 30 seconds (Pmean: +10.8%), bench press (+5.7%), squat (+23.1%), power clean (+6.1%), time to 3,000- and 30-m sprints (-3.6, -1.3% respectively). During the period that the C increased, there was no significant variation for the T. The T/C ratio followed a variation pattern contrary to that of the C. We found strong correlations between salivary T, C, and T/C and the variation in explosive strength. Our results suggest that data about subjects' salivary C, T, and T/C may be employed to optimize the training process for sports people who need to develop strength and aerobic fitness simultaneously.